Quantifying Coaching Considerations, Attitudes And Strategies To Player Substitutions In School Rugby Union - Volkwyn, Cheryl-Ann; Lombard, Adrian; Green, Andrew (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
Rugby is a high-intensity collision sport played by fifteen players in highly specialised playing positions. Due to these physical demands and to maintain a highly competitive level, a coach may substitute no more than eight players during the match. Player substitutions can affect the match’s outcome and knowing when to substitute players is largely determined by a coaches’ intuition. Therefore, the coaches’ involvements and decisions behind player changes must be assessed, as the effects of changing a player can directly affect the team’s performance. A six-sectioned questionnaire was developed to assess various issues surrounding player substitutions. Specifically, reasons for substituting players, considerations, informing players, match progression and status. Question responses followed a five-point Likert scale. Sixty-nine age-group level rugby coaches (experience 11.7 ± 9.0 years) completed the questionnaire. Common responses indicated that coaches used substitutions to increase their team’s chances of winning and to reduce player load. Additionally, the results indicate that coaches are likely to substitute players based on a predetermined strategy and to manage player loads. Coaches were likely to change players following a team scoring and as the game progressed. Additionally, substitutions were more likely when game importance increased. Finally, coaches frequently considered technical abilities of the players, timing and score of the game before changing players. The results provide a likely indication that coaches rely on their own previous playing experience regarding their decision-making approaches. Importantly, substitutions are planned and not reactive. Overall, coaches should provide sufficient notice and instruction to replacement players.